2022
DOI: 10.1136/bmjopen-2021-051267
|View full text |Cite
|
Sign up to set email alerts
|

Association of impaired kidney function with mortality in rural Uganda: results of a general population cohort study

Abstract: ObjectiveTo determine the association between baseline kidney function and subsequent all-cause mortality.Design and settingA general population-based cohort study from rural Uganda.ParticipantsPeople aged 18 years and above with measured baseline estimated glomerular filtration rate (eGFR), recruited from survey rounds in 2011–2012 or 2014–2015 and followed up to March 2019.Outcome measureThe primary outcome was all-cause mortality, identified through reports from community health workers and verified by verb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The mortality rate in our study (25 per 1000 person-years) is comparable to that reported in rural Ethiopia among TB survivors [ 3 ]. This rate is 5-9.5 times higher than the mortality rate reported in the general rural population in Uganda [ 6 , 7 ]. The high incidence of mortality is of concern since the majority of those who died were in their productive years (20-60 years of age).…”
mentioning
confidence: 66%
“…The mortality rate in our study (25 per 1000 person-years) is comparable to that reported in rural Ethiopia among TB survivors [ 3 ]. This rate is 5-9.5 times higher than the mortality rate reported in the general rural population in Uganda [ 6 , 7 ]. The high incidence of mortality is of concern since the majority of those who died were in their productive years (20-60 years of age).…”
mentioning
confidence: 66%
“…Additional studies from a rural environment in Nigeria and Tanzania have reported a higher CKD prevalence of 12.4%–27.6% not associated with diabetes, hypertension, obesity or HIV, a proxy for CKDu 24,72,81 . In a predominantly young (66% aged <45 years) rural Ugandan community, the adjusted population attributable fraction of CKD due to key risk factors was 39.2%, and CKD despite the much lower prevalence of traditional risk factors was associated with a 6‐fold risk of mortality 82,83 . Africans living in rural areas faces unique risk factors for CKDu, such as exposure to pesticides, use of traditional medicines, drinking unsafe water, unsafe storage of foodstuffs (exposure to fungi secondary products) and infections 42,44,80 .…”
Section: Resultsmentioning
confidence: 99%
“…24,72,81 In a predominantly young (66% aged <45 years) rural Ugandan community, the adjusted population attributable fraction of CKD due to key risk factors was 39.2%, and CKD despite the much lower prevalence of traditional risk factors was associated with a 6-fold risk of mortality. 82,83 Africans living in rural areas faces unique risk factors for CKDu, such as exposure to pesticides, use of traditional medicines, drinking unsafe water, unsafe storage of foodstuffs (exposure to fungi secondary products) and infections. 42,44,80 These may constitute significant CKD risk factors previously unidentified among this population, as history of exposure to pesticides and drinking unsafe water were, respectively, associated with 2.1 and 2.8-fold risks of CKDu.…”
Section: Ckd and Environmental Stressorsmentioning
confidence: 99%